2022
DOI: 10.1186/s40337-022-00579-w
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of parents and patients hospitalised in a child psychiatric unit for anorexia nervosa after reorganisation of care imposed by the COVID-19 Pandemic in France: a qualitative study—The QUALICOVID study

Abstract: Background Anorexia nervosa is a serious, albeit common mental illness that generally occurs during adolescence. Although outpatient care is recommended, hospitalisation is sometimes required. There is a dedicated hospitalisation unit caring for children and adolescents presenting with anorexia nervosa in Nancy, France. However, on 16 March 2020, a national lockdown was declared by the French government as the COVID-19 pandemic escalated in France. This resulted in the adjustment of hospital ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Will he be able to handle himself? We keep thinking, ‘Is he going to grow out of it?’” [ 43 ] “I thought the transition was a bit sudden, you know, with her coming home and having to return to school and then having to cope with everything.” [ 38 ] Experience of relapse “…deteriorating before our eyes…” “I find it quite depressing…” [ 21 ] “…taking one step forward and then three back…” [ 32 ] “… to accept relapses was difficult. To accept that it didn’t go according to the pace I had hoped…” [ 44 ] …”
Section: Thematic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Will he be able to handle himself? We keep thinking, ‘Is he going to grow out of it?’” [ 43 ] “I thought the transition was a bit sudden, you know, with her coming home and having to return to school and then having to cope with everything.” [ 38 ] Experience of relapse “…deteriorating before our eyes…” “I find it quite depressing…” [ 21 ] “…taking one step forward and then three back…” [ 32 ] “… to accept relapses was difficult. To accept that it didn’t go according to the pace I had hoped…” [ 44 ] …”
Section: Thematic Analysismentioning
confidence: 99%
“…“She’s been very relaxed over the past week… whereas she wasn’t at all before, she was self-centred” [ 38 ]…”
Section: Thematic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, studies are pointing to increased practical demands for parents caused by disruptions of daily routines both for their children (e.g., school closures) and for themselves (e.g., working‐at‐home‐orders) as well as related to COVID‐measures in the inpatient treatment setting (visiting restrictions) (Clark Bryan et al., 2020; Zeiler, Wittek, et al., 2021). Parents from UK and France also expressed worries and fears related to early discharge of patients and the anticipated resurgence of symptoms (Clark Bryan et al., 2020; Sourlier et al., 2022). Two qualitative studies found that parents felt relieved having more time to provide practical and emotional support for their affected child while caregiving tasks were also experienced more intense and exhausting (Shaw et al., 2021; Sourlier et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Parents from UK and France also expressed worries and fears related to early discharge of patients and the anticipated resurgence of symptoms (Clark Bryan et al., 2020; Sourlier et al., 2022). Two qualitative studies found that parents felt relieved having more time to provide practical and emotional support for their affected child while caregiving tasks were also experienced more intense and exhausting (Shaw et al., 2021; Sourlier et al., 2022). This ambiguity is somehow reflected by a quantitative survey conducted in Ireland between September 2020 and March 2021 showing that approximately the same percentage of parents and other caregivers (one third to a half depending on the time point) agreed and disagreed with the statement that the pandemic has made it harder for them to provide support for the person with the eating disorder (Parsons et al., 2021).…”
Section: Introductionmentioning
confidence: 99%